2017
DOI: 10.5014/ajot.2017.024976
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Pediatric Game-Based Neurorehabilitation Using Telehealth Technologies: A Case Report

Abstract: This case report is the first in a series of reports designed to determine the feasibility of implementing game-based neurorehabilitation using telehealth technologies (GbN+TT) for children with cerebral palsy, evaluate the responsiveness of relevant outcome measures to changes in motor impairment and activity participation after intervention, and identify technological challenges associated with implementation of GbN+TT. The participant completed more than 56 hr of game-based neurorehabilitation over 8 wk usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 30 publications
0
33
2
Order By: Relevance
“…The evidence literature provides support for the use of a telehealth service-delivery model in occupational therapy (OT) practice within various settings. The use of telehealth in pediatric occupational therapy has been shown to be effective by increasing access to specialist care and preventing delays in provision of services (Cason, 2014), increasing collaboration and carry-over of treatment strategies (Gibbs & Toth-Cohen, 2011), and improving overall therapist/client satisfaction (Ashburner, 2016;Criss, 2013;Reifenberg, et al, 2017;Zylstra, 2013). Despite the effectiveness of a telehealth service-delivery model, the use of telehealth in occupational therapy practice is limited, potentially due to a lack of knowledge about telehealth.Education is a critical factor necessary to promote successful implementation of telehealth in clinical practice (Nissen & Brockevelt, 2016).…”
mentioning
confidence: 99%
“…The evidence literature provides support for the use of a telehealth service-delivery model in occupational therapy (OT) practice within various settings. The use of telehealth in pediatric occupational therapy has been shown to be effective by increasing access to specialist care and preventing delays in provision of services (Cason, 2014), increasing collaboration and carry-over of treatment strategies (Gibbs & Toth-Cohen, 2011), and improving overall therapist/client satisfaction (Ashburner, 2016;Criss, 2013;Reifenberg, et al, 2017;Zylstra, 2013). Despite the effectiveness of a telehealth service-delivery model, the use of telehealth in occupational therapy practice is limited, potentially due to a lack of knowledge about telehealth.Education is a critical factor necessary to promote successful implementation of telehealth in clinical practice (Nissen & Brockevelt, 2016).…”
mentioning
confidence: 99%
“…The games have levels as the child performs well at the previous level. It is a supportive tool to strengthen children's motor, cognitive and communicative skills (TRESSER, 2012;CABRAL et al, 2016;REIFENBERG et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies like Tresser´s study (2012) who used the Timocco platform with a child of 5 years and 2 months old, diagnosed with dyspraxia, used the game Falling fruit; Reifenberg et al (2017) study used the platform in the rehabilitation work of a child with cerebral palsy in their home; and Benham and Gibbs (2017) study used it with two children aged 5 and 7 years old, with difficulties in fine motor coordination, carried out at school, showed that the use of playful tools in working with children with disabilities increases the interest and motivation in performing rehabilitation activities through games, and the use of the Timocco Platform enabled the development of motor coordination skills.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations